The Representation of Professional Attitude, Professional Integrity, and Human Resource Capability on Customer Satisfaction at BPJS Ketenagakerjaan Bandar Lampung with Interpersonal Communication as a Moderating Variable - Monica Adelia; Febrianty; Ayu Nursari (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the influence of professional attitude, professional integrity, and human resource capabilities on the satisfaction of BPJS Ketenagakerjaan customers in Bandar Lampung, with interpersonal communication as a moderating variable. The background of the research is based on the increasing demands for the quality of public services, which depend not only on the competence and ethics of employes, but also on the dynamics of interaction between employes and customers. This research uses a quantitative approach with a survey method applied to BPJS Ketenagakerjaan customers in Bandar Lampung, while data analysis is performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The research results indicate that professional attitude, professional integrity, and human resource capabilities have a positive and significant impact on customer satisfaction. However, interpersonal communication was found to act as a moderating variable, weakening the influence of professional attitude, professional integrity, and human resource capabilities on customer satisfaction. This finding indicates that less effective communication quality can reduce the positive impact of employe professionalism, integrity, and capabilities in shaping customer satisfaction. This research provides an empirical contribution to the study of human resource management in the public sector and serves as a basis for BPJS Ketenagakerjaan in formulating more adaptive human resource development policies and service communication strategies that are customer-oriented.